2018
DOI: 10.1007/s10597-018-0288-y
|View full text |Cite|
|
Sign up to set email alerts
|

Veteran Coffee Socials: A Community-Building Strategy for Enhancing Community Reintegration of Veterans

Abstract: Veterans transitioning from military to civilian life are vulnerable to a loss of social support and an increase in isolation from their communities, which can exacerbate other difficulties they may be experiencing, such as physical or mental health problems. Veteran Coffee Socials are an innovative community-building pilot intervention designed to foster social support and community between veterans. In seven target communities, certified peer specialists initiated and facilitated weekly "Veteran Coffee Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…This is an important finding since many veterans struggle to develop connections with others who have never served in the military (Ahern et al, 2015) but still wish to develop this type of camaraderie in their civilian life. Consistent with previous research (Gorman et al, 2018; Jain et al, 2016; Laffaye et al, 2008), veterans reported that their relational bonds were strongest with other veterans in OH. This provides additional support for the veteran identity as particularly central to veterans’ self‐conceptualization (Hart & Lancaster, 2019; Nichols, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…This is an important finding since many veterans struggle to develop connections with others who have never served in the military (Ahern et al, 2015) but still wish to develop this type of camaraderie in their civilian life. Consistent with previous research (Gorman et al, 2018; Jain et al, 2016; Laffaye et al, 2008), veterans reported that their relational bonds were strongest with other veterans in OH. This provides additional support for the veteran identity as particularly central to veterans’ self‐conceptualization (Hart & Lancaster, 2019; Nichols, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Improved social connectedness and wellbeing has also been reported among contemporary ex-serving Australian veterans who participated in a peer outdoor support therapy program [ 85 ]. Research is also emerging in support of the improved social connectedness among ex-serving veterans attending programs without a clinical focus such as social networking groups [ 85 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a sense of social connectedness is not fixed, and can be established where individuals experience trusting relationships, are not rejected, and feel a sense of collective identity [31]. As such, peer-support and group-based behavioural activation programs provide striking examples of how military identity and social connectedness may interrelate to influence wellbeing [81][82][83][84][85][86][87][88][89][90]. For instance, veteran-centred therapeutic horseback riding [88], surfing [89], and group exercise programs [86] have demonstrated an ability to reduce PTSD symptoms and improved social connectedness among ex-serving US veterans.…”
Section: Plos Onementioning
confidence: 99%
“… 6 These should include creative opportunities for community and connection among veterans 51 —for example, recreational gatherings or collaborative volunteer opportunities. 52 …”
Section: Discussionmentioning
confidence: 99%